‘It could be effective…’: Uncertainty and over-promotion in the abstracts of COVID-19 preprints - Bordignon, Frédérique (London School of Economics and Political Science Research Online (London School of Economics and Political Science), 2022)
A defining feature of the impact of the COVID-19 pandemic on scholarly communication has been the brief and intense surge in the production of preprints. This has had significant impacts on the ways in which new research findings have been reported and communicated more broadly and the role played by abstracts in highlighting the meaning and value of new research. Based on a study of the language deployed in the abstracts of recently published COVID-19 preprints, Frédérique Bordignon, Liana Ermakova and Marianne Noël, argue two defining features of these abstracts are over-promotion and hedging, a deliberate ambiguity that suggests authors should pay greater attention to what they seek to communicate in their abstracts.